Urgensi Dalalah dalam Kajian UshulFiqh - Kadir, Abdul (At-Tawazun, Jurnal Ekonomi Syariah, 2020)
Islamic law is rooted in the Qur'an and al-Sunnah. The two sources of law, after the death of the Prophet Muhammad, did not change or increase at all. while the problems that occur in the midst of the ummah are always changing. Therefore, a deep understanding of the sources of Islamic law is a necessity. One of the efforts to find laws or rules contained in the sources of Islamic law is through understanding the language instructions (dalalah al-lafzi). Understanding of linguistic instructions is not only in the form of express understanding, but can also be understood implicitly what is contained in the language of the texts (al-Qur'an or al-Sunnah). There are several kinds of ways or methods of understanding texts through language instructions. Each method or method has different implications for understanding each other. With a deep understanding of language instructions with various theories or ways of understanding, Islamic law can be understood to lead to a comprehensive understanding